Synthesis of Tricyclic Derivatives of Antitumor Alkaloid Ellipticine - Ergün, Yavuz; Gülle, Sibel; Çagdas Bilici, Adil; Göçmentürk, Mustafa; Okay, Gürol (Asian Journal of Chemistry, 2010)
The synthesis of tricyclic analogue of ellipticine, 3-[N-(2-hydroxy-ethyl)aminomethyl]-4- methyl-9H-carbazole (10) has been achieved. In this study, new carbazole and tetrahydrocarbazole derivatives (3, 4, 7 and 9) have also been synthesized.